Relation between downward and upward phases on the trampoline bed during jumping - Matsushima, M. (Science of Gymnastics Journal, 2023)
The time of flight in trampoline competitions relies on the jumping movement executed on the trampoline bed, which can be divided into a downward phase and an upward phase. These two phases of the jumping movement exhibit distinct characteristics. Therefore, the aim of this study was to investigate fundamental data regarding the vertical deflection length, time, velocity, and force involved in the vertical movement on the trampoline bed. The study involved ten trampoline athletes, including participants in the All Japan Championships and members of the Japanese national team. These athletes were instructed to perform 15 consecutive jumps on the trampoline bed, starting from a standing-still position, aiming for maximum height, and maintaining a straight trajectory in the center of the trampoline bed.